Amiodarone associated alveolitis and polyarthropathy. Treatment by plasma exchange. - Russell, D C (1983)
In a case of severe alveolitis and polyarthropathy occurring within two to five months of starting amiodarone treatment high plasma concentrations of immune complexes were found, suggesting a drug mediated hypersensitivity reaction. Initial symptomatic response followed high dosage corticosteroid and immunosuppressant treatment, but reduction in the dosage of corticosteroids was achieved only by successive plasma exchange with concomitant reduction in plasma concentrations of both amiodarone and immune complexes.